2004
DOI: 10.1007/s00213-003-1696-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periadolescent versus adult cocaine exposure on cocaine conditioned place preference and motor sensitization in mice

Abstract: Our results are consistent with a "vulnerable brain" hypothesis for responses to cocaine based on our findings that periadolescent mice exhibit greater locomotor sensitization to cocaine, and greater baseline anxiety responses that are alleviated by cocaine exposure compared to adult mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
4
27
0
1
Order By: Relevance
“…All animals, irrespective of dose, age, or housing condition, acquired a marked cocaine-CPP, with the exception of the adolescent isolated mice conditioned with the lower dose of cocaine. Age-related differences in cocaine-induced CPP have been reported in rats (Brenhouse and Andersen 2008) but not in mice (Balda et al 2006;Campbell et al 2000;Schramm-Sapyta et al 2004), as we have observed in this study. The lack of dose effects also confirms previous results regarding cocaine-CPP (Maldonado et al 2006).…”
Section: Discussionsupporting
confidence: 73%
“…All animals, irrespective of dose, age, or housing condition, acquired a marked cocaine-CPP, with the exception of the adolescent isolated mice conditioned with the lower dose of cocaine. Age-related differences in cocaine-induced CPP have been reported in rats (Brenhouse and Andersen 2008) but not in mice (Balda et al 2006;Campbell et al 2000;Schramm-Sapyta et al 2004), as we have observed in this study. The lack of dose effects also confirms previous results regarding cocaine-CPP (Maldonado et al 2006).…”
Section: Discussionsupporting
confidence: 73%
“…Various findings have been reported for locomotor activity in drug-naïve adolescent and adult rats. Lower (Adriani & Laviola, 2000;Schramm-Sapyta, Pratt, & Winder, 2004) and higher (Spear & Brake, 1983;Stansfield & Kirstein, 2006) levels of locomotor activity were reported for naïve adolescent relative to naïve adult rodents. Differences in novel environment-induced locomotor activity between adolescent and adults have been previously attributed to adolescents perceiving a novel environment as less stressful than adults and were supported by the fact that adolescents have greater basal corticosterone levels and a hyposensitive neuroendocrine and stress response system at this relatively young developmental stage (Adriani & Laviola).…”
Section: Discussionmentioning
confidence: 87%
“…in a saline vehicle in a volume of 10 mL/kg body weight based on previous experiments in adult mice (Schramm-Sapyta et al 2004). For cocaine CPP and fear extinction, yohimbine was administered (i.p.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…The apparatus was as previously described (Schramm-Sapyta et al 2004). Med Associates open field chambers were fitted with acrylic inserts that created two distinct environments.…”
Section: Cocaine Cpp and Extinctionmentioning
confidence: 99%